Diseño de una línea de respaldo para el proceso de compresión de gas natural de la unidad de servicios industriales en Ecopetrol en Cartagena de Indias (2023)
The present investigation is developed with the intention of providing an applicable and detailed solution to a problem found inside the Ecopetrol S.A. refinery, whose purpose is to work with hydrocarbons and gases, being this one of the flagship companies of Colombia and with greater economic impact on the country. Within the processes carried out by the company, it is necessary to do every 24 thousand working hours, maintenance must be carried out, which implies one of the compressors is assisted, while the other sustains all the load and demand of the refinery processes. . Due to the above, this document proposes the design of a backup line for the natural gas compressors of the Ecopetrol Industrial Services Unit, to guarantee the continuity of the process, improvement of productivity and prevention of total shutdown of the refinery located in Cartagena de Indias.